High-rate graphite negative electrode material and preparation method thereof

By growing carbon nanotubes on the surface of graphite materials, the conductivity and rate performance of the negative electrode of lithium-ion batteries are improved, and the problems of insufficient conductivity and cycle stability of the negative electrode materials in the prior art are solved, thereby achieving high efficiency and high energy density Battery performance.

CN119181783APending Publication Date: 2024-12-24HUNAN CHMM-SUNWARDS NEW MATERIAL CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411104373.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-13
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

The existing lithium-ion battery anode materials have shortcomings in terms of high magnification and first-time efficiency, resulting in poor battery cycle life and stability, especially the first-time efficiency of artificial graphite surface coating materials, which affects the energy density of the entire battery.

Method used

Chemical vapor deposition of carbon nanotubes is formed by immersing the graphite material in a ferrocene solution and then depositing it on standby at room temperature to form a high-ratio graphite negative electrode material covered with carbon nanotubes, improving conductivity and rate performance.

Benefits of technology

The conductivity and rate performance of the graphite negative electrode are significantly improved, the first charge and discharge efficiency reaches more than 95%, the capacity retention rate of 500 cycles is greater than 90%, and excellent stability is shown in low-temperature cycles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119181783A_ABST
    Figure CN119181783A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a high-rate graphite negative electrode material. The preparation method comprises the following steps: S1, soaking a prepared graphite material in a ferrocene solution for 2-6 hours; s2, standing and depositing the solution soaked in the step S1 at room temperature, cleaning with deionized water, performing suction filtration, and drying at 80-120 DEG C; and S3, carrying out carbon nanotube growth on the graphite material dried in the step S2, so that the carbon nanotubes grow on the surface of the graphite material to obtain the high-magnification graphite negative electrode material with the surface coated with the carbon nanotubes. After the graphite is soaked in the ferrocene solution, the growth of the carbon nanotubes on the surface of the graphite is facilitated; the grown carbon nanotubes are dispersed on the surface of the graphite more uniformly, and a graphite material with excellent two-dimensional performance is converted into a carbon material with excellent three-dimensional performance, so that the conductivity of the graphite negative electrode is remarkably improved, and the rate capability of the graphite negative electrode is effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium battery negative electrode materials, and in particular to a high-rate graphite negative electrode material and a preparation method thereof. Background Art

[0002] Carbon materials have the advantages of high lithium storage capacity, abundant raw materials, low electrode potential, low cost, non-toxicity and stability, and have been rapidly developed. The carbon negative electrode materials of lithium-ion batteries are mainly natural graphite and artificial graphite. With the increasing requirements of lithium-ion batteries for negative electrode energy density, the negative electrode materials are required to have high specific capacity while improving the initial efficiency of the materials, and improving the full battery positive electrode capacity and the energy density of the whole battery.

[0003] At present, the negative electrode materials on the market are mainly artificial graphite, and the surface coating material is soft carbon / hard carbon material. The first efficiency of artificial graphite is between 91-94%, especially for the positive electrode LFP system (first efficiency above 96%), which causes the first efficiency of the whole battery to be low and affects its energy density. The reason is that the soft carbon or hard carbon coated on the surface of artificial graphite has low specific capacity and low first efficiency (300mAh / g, 80%). One of the measures to improve the first efficiency of the material is to coat the graphite surface with carbon-based / non-carbon-based materials with high first efficiency and good kinetics without reducing the energy density of the material.

[0004] At present, the modification technology of carbon negative electrode materials mainly uses multiphase coating technology to construct core-shell structure, doping, surface oxidation, etc., to improve electrochemical performance. However, there are still many problems, such as poor contact between electrode material particles and between electrode material particles and current collectors, large surface resistance, poor peel strength, and cyclic expansion during charge and discharge. The above problems seriously affect the cycle life and stability of lithium-ion batteries. Summary of the invention

[0005] The main purpose of the present invention is to provide a high-rate graphite negative electrode material and a preparation method thereof, so as to enhance the conductivity of the graphite negative electrode, improve the rate performance and the initial efficiency.

[0006] To achieve the above object, the present invention provides a method for preparing a high-rate graphite negative electrode material, comprising the steps of:

[0007] S1, soaking the prepared graphite material in a 0.1-0.5 mol / L ferrocene solution for 2-6 hours;

[0008] S2, allowing the solution soaked in step S1 to stand and settle at room temperature, then washing with deionized water, filtering and drying at 80-120° C.;

[0009] S3, growing carbon nanotubes on the graphite material dried in step S2, so that carbon nanotubes grow on the surface of the graphite material to obtain a high-rate graphite negative electrode material with the surface coated with carbon nanotubes.

[0010] Furthermore, the graphite material in step S1 is one or more of natural flake graphite, microcrystalline graphite, crystalline vein graphite, artificial graphite, natural spherical graphite, mesophase carbon microspheres, conductive graphite, graphene and graphite fiber.

[0011] Furthermore, the concentration of the ferrocene solution is 5% to 15%.

[0012] Furthermore, the carbon nanotube growth method in step S3 is to in-situ grow carbon nanotubes on the surface of the graphite material by chemical vapor deposition.

[0013] Furthermore, before step S1, the method further includes the steps of cleaning and roughening the graphite material.

[0014] Furthermore, the step of cleaning and roughening the graphite material includes: placing the graphite in an acetone solution, ultrasonically cleaning and drying it, and then roughening the dried graphite material at 300-400° C. for 15-60 minutes.

[0015] Furthermore, step S3 includes: heating to 300-450°C in an argon atmosphere, replacing argon with hydrogen, keeping the temperature at this temperature for a period of time, then heating to 600-900°C, introducing methane and argon, keeping the temperature, then turning off the methane gas, cooling to room temperature under the protection of argon, and growing carbon nanotubes in situ on the surface of the graphite material.

[0016] Furthermore, the present invention also provides a high-rate graphite negative electrode material, which is prepared by the preparation method as described in any one of the above claims.

[0017] The present invention also provides a negative electrode current collector for a lithium ion battery, the negative electrode current collector comprising: a conductive substrate and a negative electrode slurry layer coated on one or both sides of the conductive substrate, the negative electrode slurry layer being prepared by any of the preparation methods described above.

[0018] The present invention further provides a lithium ion battery, comprising a positive electrode, an electrolyte and a negative electrode, characterized in that the negative electrode comprises the lithium ion battery negative electrode collector as described above.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] (1) After graphite is immersed in ferrocene solution, it is beneficial to the growth of carbon nanotubes on the graphite surface;

[0021] (2) The grown carbon nanotubes are more evenly dispersed on the graphite surface, and the graphite material with two-dimensional excellent properties is transformed into a carbon material with three-dimensional excellent properties;

[0022] (3) Due to the introduction of carbon nanotubes, the conductivity of the graphite negative electrode has been significantly improved, and its rate performance has been effectively improved. Its first charge and discharge efficiency is as high as 95% or more, and the capacity retention rate after 500 cycles is greater than 90%. Compared with the prior art, the present invention has the characteristics of high first charge and discharge efficiency and excellent high and low temperature cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.

[0024] Figure 1 This is the SEM image of the graphite without growing carbon nanotubes in Comparative Example 1.

[0025] Figure 2 This is the SEM image of carbon nanotube graphite directly grown in comparative example 2.

[0026] Figure 3 This is the SEM image of physically mixed graphite and carbon nanotubes in comparative example 3.

[0027] Figure 4 This is a SEM image of carbon nanotube graphite grown after soaking in ferrocene in Example 1. DETAILED DESCRIPTION

[0028] The technical solution in this embodiment will be described clearly and completely below in conjunction with the drawings in this embodiment. Obviously, the described embodiment is only a part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] In addition, the technical solutions between the various embodiments of the present invention can be combined with each other, but it must be based on the fact that ordinary technicians in the field can implement it. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such combination of technical solutions does not exist and is not within the scope of protection required by the present invention.

[0030] It should be understood that the specific embodiments described herein are only used to explain the present invention, and are not used to limit the present invention.

[0031] Comparative Example 1

[0032] Artificial graphite with a carbon content of more than 85% and a particle size of 3 to 40 μm.

[0033] Comparative Example 2

[0034] 2 g of the artificial graphite in Comparative Example 1 was heated to 350°C in an argon atmosphere, argon was replaced by hydrogen, and the temperature was maintained for a period of time. The temperature was then raised to 800°C, methane and argon were introduced, and the temperature was maintained. The methane gas was then turned off, and the mixture was cooled to room temperature under the protection of argon to grow carbon nanotubes in situ on the surface of the graphite material.

[0035] Comparative Example 3

[0036] 1 g of carbon nanotubes is dispersed in deionized water containing 1% by mass of surfactant hexadecyltrimethylammonium bromide (HTAB), and the carbon nanotubes are uniformly dispersed in the dispersant by ultrasonic treatment for 60 minutes; 4 g of graphite is uniformly dispersed in the carbon nanotube dispersion, and the temperature is controlled at 80-95° C. until the dispersant is evaporated; high-temperature calcination is performed at 500° C. to carbonize the residual dispersant and surfactant in the carbon nanotube dispersion, and a graphite negative electrode material of physically mixed graphite and carbon nanotubes is obtained after crushing.

[0037] Example 1

[0038] S1, soaking 2 g of the artificial graphite in Comparative Example 1 in 50 ml of 0.2 mol / L ferrocene solution for 4 h;

[0039] S2, leaving the solution after immersion in step S1 to stand at room temperature for 4 hours, then washing with deionized water, filtering and drying at 110° C.;

[0040] S3, growing carbon nanotubes on the graphite material dried in step S2, heating it to 350°C in an argon atmosphere, replacing argon with hydrogen, keeping it at this temperature for a period of time, then heating it to 800°C, introducing methane and argon, keeping it warm, then turning off the methane gas, cooling it to room temperature under the protection of argon, and growing carbon nanotubes in situ on the surface of the graphite material.

[0041] Example 2

[0042] S1, soaking 2 g of the artificial graphite in Comparative Example 1 in 50 ml of 0.25 mol / L ferrocene solution for 4 h;

[0043] S2, leaving the solution after immersion in step S1 to stand at room temperature for 4 hours, then washing with deionized water, filtering and drying at 110° C.;

[0044] S3, growing carbon nanotubes on the graphite material dried in step S2, heating it to 350°C in an argon atmosphere, replacing argon with hydrogen, keeping it at this temperature for a period of time, then heating it to 800°C, introducing methane and argon, keeping it warm, then turning off the methane gas, cooling it to room temperature under the protection of argon, and growing carbon nanotubes in situ on the surface of the graphite material.

[0045] Example 3

[0046] S1, soaking 2 g of the artificial graphite in Comparative Example 1 in 50 ml of 0.1 mol / L ferrocene solution for 4 h;

[0047] S2, leaving the solution after immersion in step S1 to stand at room temperature for 4 hours, then washing with deionized water, filtering and drying at 110° C.;

[0048] S3, growing carbon nanotubes on the graphite material dried in step S2, heating it to 350°C in an argon atmosphere, replacing argon with hydrogen, keeping it at this temperature for a period of time, then heating it to 800°C, introducing methane and argon, keeping it warm, then turning off the methane gas, cooling it to room temperature under the protection of argon, and growing carbon nanotubes in situ on the surface of the graphite material.

[0049] Please refer to Figure 1-4 It can be seen that after soaking the graphite in ferrocene solution, the direct physical mixing of the growth arms of the carbon nanotubes on the graphite surface is more uniform and has a larger coverage area; the grown carbon nanotubes are more evenly dispersed on the graphite surface, transforming the graphite material with two-dimensional excellent properties into a carbon material with three-dimensional excellent properties.

[0050] The electrical performance tests were performed on Comparative Examples 1-3 and Example 1.

[0051] At room temperature, a binder, a conductive agent and a solvent were added to the graphite negative electrode materials of Example 1 and Comparative Examples 1-3, stirred to make a slurry, coated on a copper foil, and dried and rolled to obtain a negative electrode sheet; the binder used was PVDF, the conductive agent was conductive carbon black (SP), the solvent was N-methylpyrrolidone (NMP), and the amount ratio of the negative electrode material, SP, PVDF, and NMP was 95g:1g:4g:200mL.

[0052] In the electrolyte, LiPF6 is the electrolyte, and a mixture of EC and DEC with a volume ratio of 1:1 is the solvent.

[0053] The metal lithium sheet is the counter electrode and the diaphragm is made of polypropylene (PP) film.

[0054] Test conditions: charge and discharge voltage range is 0.005V~2.0V, charge and discharge rate is 0.1C. At the same time, the rate (2C / 0.2C), rate (5C / 0.2C) and cycle performance (0.2C / 0.2C, 1000 cycles) were tested.

[0055] The test results are as follows:

[0056]

[0057] It can be seen from the above that the first discharge specific capacity and first efficiency of Example 1 are better than those of Comparative Examples 1-3, the grown carbon nanotubes are evenly dispersed on the graphite surface, and the graphite material with two-dimensional excellent properties is transformed into a carbon material with three-dimensional excellent properties. The three-dimensional structure can increase the lithium ion insertion and extraction rate of the material, improve the rate and increase the energy density.

[0058] The above are only preferred embodiments of the present invention, and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A method for preparing a high-rate graphite negative electrode material, characterized in that: Includes steps: S1, soaking the prepared graphite material in a 0.1-0.5 mol / L ferrocene solution for 2-6 hours; S2, allowing the solution soaked in step S1 to stand and settle at room temperature, then washing with deionized water, filtering and drying at 80-120° C.; S3, growing carbon nanotubes on the graphite material dried in step S2, so that carbon nanotubes grow on the surface of the graphite material to obtain a high-rate graphite negative electrode material with the surface coated with carbon nanotubes.

2. The method according to claim 1, characterized in that The graphite material in step S1 is one or more of natural flake graphite, microcrystalline graphite, crystalline vein graphite, artificial graphite, natural spherical graphite, mesophase carbon microspheres, conductive graphite, graphene and graphite fiber.

3. The method according to claim 2, characterized in that The concentration of the ferrocene solution is 5% to 15%.

4. The method according to claim 1, characterized in that: The carbon nanotube growing method in step S3 is to grow carbon nanotubes in situ on the surface of the graphite material by chemical vapor deposition.

5. The method according to claim 4, characterized in that The step S1 also includes the step of cleaning and roughening the graphite material.

6. The method according to claim 5, characterized in that The step of cleaning and roughening the graphite material comprises: placing the graphite in an acetone solution, ultrasonically cleaning and drying, and then roughening the dried graphite material at 300-400° C. for 15-60 minutes.

7. The method according to claim 4, characterized in that The step S3 comprises: heating to 300-450° C. in an argon atmosphere, replacing argon with hydrogen, keeping the temperature at this temperature for a period of time, then heating to 600-900° C., introducing methane and argon, keeping the temperature, then turning off the methane gas, cooling to room temperature under the protection of argon, and growing carbon nanotubes in situ on the surface of the graphite material.

8. A high-rate graphite negative electrode material, characterized in that: The method is prepared according to any one of claims 1 to 8.

9. A negative electrode current collector for a lithium ion battery, characterized in that: The negative electrode current collector comprises: a conductive substrate and a negative electrode slurry layer coated on one side or both sides of the conductive substrate, wherein the negative electrode slurry layer is prepared by the preparation method according to any one of claims 1 to 7.

10. A lithium ion battery comprising a positive electrode, an electrolyte and a negative electrode, characterized in that: The negative electrode comprises the negative electrode current collector of the lithium ion battery as claimed in claim 9.

Citation Information

Cited By

  • Multi-conductive-agent composite conductive slurry for lithium battery and preparation method of multi-conductive-agent composite conductive slurry

    CN121394405A